Caring for a child with an eating disorder: Understanding differences among mothers and fathers of adolescent and adult children. (25th June 2022) - Stillar, Amanda; Merali, Noorfarah; Gusella, Joanna; Scarborough, Jennifer; Nash, Patricia; Orr, Emily; Henderson, Katherine; Mayman, Shari; Files, Natasha; Lafrance, Adele
Abstract: Objective: This study investigated treatment‐engagement fears, self‐efficacy, and accommodating and enabling in mothers and fathers of adolescent and adult children with eating disorders. Methods: This study involved a secondary analysis of pre‐treatment data from a subsample of 143 parents (95 mothers; 48 fathers) from a Canada‐wide multi‐site study. Parents completed the Caregiver Traps Scale, Parents Versus Anorexia Scale, and the Accommodation and Enabling Scale for Eating Disorders. Data were analysed using factorial Multivariate Analysis of Variance and mediation via multiple regression. Results: Mothers reported higher levels of treatment‐engagement fears than fathers. Among mothers, higher fear predicted lower self‐efficacy and more accommodating and enabling behaviours. Among fathers, neither fear nor self‐efficacy predicted accommodating and enabling. No differences in treatment‐engagement fear or self‐efficacy between parents of adolescent child and adult children were found at pre‐treatment. Conclusions: Mothers' and fathers' experience different levels of fear related to their involvement in their ill‐child's treatment at pre‐treatment, and that fear is uniquely related to variables that impact treatment outcomes. There is a need to support parents even when their child is an adult. This study can inform family‐based treatments vis‐a‐vis tailoring interventions for mothers and fathers and providing support to parents of children with eating disorders across the lifespan. Key points: Mother's experience higher levels of fear related to their involvement in their child's treatment than fathers at pre‐treatment. Fear predicted self‐efficacy and accommodating and enabling behaviours among mothers whereas neither fear nor self‐efficacy predicted accommodating and enabling behaviours among fathers. Parents of adult children experience the same degree of treatment‐engagement fear and self‐efficacy than parents of adolescent children.